Post-vaccination campaign evaluation of systemic and mucosal immunity of trivalent oral poliovirus vaccine in Karachi, Pakistan (2020–2021): a cross-sectional studyResearch in context - Ali Faisal Saleem; Visalakshi Jeyaseelan; Zaubina Kazi; Mahjabeen Zehra; Muhammad Masroor Alam; Grace Macklin; Rocio Lopez Cavestany; Sajid Muhammad; Najeeb Rehman; Ondrej Mach (The Lancet Regional Health - Southeast Asia)
Summary: Background: The transmission of wild poliovirus (WPV1) and circulating vaccine-derived poliovirus (cVDPV) continues to be a major Public Health Emergency of International Concern. Currently, only Afghanistan and Pakistan remain polio-endemic for WPV1. In response to the co-circulation of VDPV2 with WPV1, the Technical Advisory Group of WHO had recommended two nationwide campaigns of trivalent oral poliovirus vaccine (tOPV) for children aged <5 years in Pakistan in 2020. We assessed the humoral and mucosal immune responses in children who received two doses of tOPV (during vaccination campaigns) in Karachi, Pakistan. Methods: A cross-sectional survey was conducted in four peri-urban sites (Cattle Colony, Ibrahim Hyderi, Ali Akber Shah, Rehri Goth) Karachi, Pakistan. Venous blood samples from children aged between 1 month and 5 years were obtained. Children who were acutely ill, requiring hospitalisation, with primary immunodeficiency, or with a chronic medical illness, were excluded from the study. Stool and serum testing was performed at the National Institute of Health, Pakistan. Sera samples were analysed using microneutralization assays to quantify polio antibodies for all three serotypes: type 1, 2, and 3. The stool samples collected at baseline, 7, 14, and 28 days (after each tOPV dose) were tested for the presence of poliovirus. Findings: Of 285 eligible children, 225 had received both tOPV doses and provided three analysable blood samples, and 193 children provided seven viable stool samples. The seroconversion rate for type 2 was 72% (44/61, 95% CI: 59.8–81.8) after the first tOPV dose; cumulative seroconversion after two doses was 93.4% (95% CI: 84.3–97.4). Seven days after the first and second tOPV campaigns, 32.7% and 18.6% excreted Sabin (vaccine) poliovirus type 2, respectively. Interpretation: The study demonstrated enhanced mucosal immunity as well as a high type 2 seroconversion rate and antibody seroprevalence after two tOPV campaigns. Funding: WHO, Geneva, Switzerland.